Low-Cost Desktop-Based Three-Dimensional-Printed Patient-Specific Craniofacial Models in Surgical Counseling, Consent Taking, and Education of Parent of Craniosynostosis Patients: A Comparison With Conventional Visual Explanation Modalities. Issue 6 (September 2019) - Alshomer, Feras; AlFaqeeh, Faisal; Alariefy, Mohammed; Altweijri, Ikhlass; Alhumsi, Taghreed
Abstract : Background: Craniosynostosis is a complex craniofacial deformity. Surgical decision, if needed, is always hard on the parent and requires the use of multimodalities of explanation. To the authors' knowledge, there have been no studies tackling family counseling about the deformity and surgical decision-making process with the use of low-cost patient-specific three-dimensional (3D)-printed models. Methods: A cross-sectional study investigating the utility of patient-specific 3D-printed models using a desktop-based 3D printer. Questionnaire was constructed and validated screening the demographics, knowledge, expectation, and surgical decision-making process supplied using Likert. Data were collected consecutively from each parent first after explanation with conventional 3D computed tomography (CT) images, and then repeated after the 3D-printed model has been presented. Results: Fourteen parents were screened. Majority of parents considered the pathology to have a potential effect of child's functional and aesthetic outcomes. After using the 3D-printed models, the participants had a clear vision and needed not to read any more about the condition ( P = 0.05, P = 0.019, respectively). Agreement for surgical management was in favor of the 3D-printed models compared with CT images ( P = 0.028). Explanation with CT images yielded higher mean score in knowledge about potential complications compared with 3D models ( P value = 0.007). For the 3D models, average printing time was 26 hours, and a mean cost of 5.2. Conclusion: The utility of desktop 3D printing is an affordable modality to provide adequate information about craniosynostosis and can assist surgical decision-making. Knowledge and adaptation of such cheap technology represents a great skill aiding clinical practice. Abstract : Supplemental Digital Content is available in the text